Chromosomal mapping of genes encoding subunits of complex I from Neurospora crassa - F Ferreirinha; T ALMEIDA; M DUARTE; AVIDEIRA (Fungal Genetics Reports, 1998)
The genes encoding the 21 kDa protein and the 19.3 kDa, 21.3 kDa and 24 kDa iron-sulfur subunits of complex I were located, by RFLP analysis, in Linkage Groups IV, VI, VI and V, respectively, of the Neurospora crassa genome